2020
DOI: 10.3390/ma13163631
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition in Iron Thin Films Containing Coherent Twin Boundaries: A Molecular Dynamics Approach

Abstract: Using molecular dynamics (MD) simulation, the austenitic and martensitic phase transitions in pure iron (Fe) thin films containing coherent twin boundaries (TBs) have been studied. Twelve thin films with various crystalline structures, thicknesses and TB fractions were investigated to study the roles of the free surface and TB in the phase transition. In the austenitic phase transition, the new phase nucleates mainly at the (112)bcc TB in the thicker films. The (111¯)bcc free surface only attends to the nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…Thus, it could be concluded that the Meyer-Entel potential might be the only one in the EAM class, which can describe both the austenitic and martensitic phase transitions. Here, we should mention that the equilibrium transition temperature of 550 ± 50 K predicted by the Meyer-Entel potential [20] differs from the experimental value of 1184 K. This is due to the fact that this potential does not include the magnetic entropy, which stabilizes the bcc phase at low temperatures [10,28]. However, it has been confirmed that the transition mechanism will not be affected by this inexact transition temperature [2][3][4]19,21,28].…”
Section: Simulation Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…Thus, it could be concluded that the Meyer-Entel potential might be the only one in the EAM class, which can describe both the austenitic and martensitic phase transitions. Here, we should mention that the equilibrium transition temperature of 550 ± 50 K predicted by the Meyer-Entel potential [20] differs from the experimental value of 1184 K. This is due to the fact that this potential does not include the magnetic entropy, which stabilizes the bcc phase at low temperatures [10,28]. However, it has been confirmed that the transition mechanism will not be affected by this inexact transition temperature [2][3][4]19,21,28].…”
Section: Simulation Methodsmentioning
confidence: 84%
“…Firstly, it is not unexpected that new phase nucleates at the intersection site between two types of defects, in our case the free surface and the phase boundary. This area provides the largest energetic and structural fluctuations for the new phase nucleation [10]. Here, two values should be given: The phase boundary energy with the N-W geometry amounts to 3.84 J/m 2 (0.96 J/m 2 ) with (without) considering the misfit dislocations [31] and the surface energy of the (111) fcc surface is 1.40 J/m 2 [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations